The Effect of Business Ethics and Social Responsibility Relationships on Consumer Satisfaction of BumDes Agrotourism Petik Melon - Novita, Mega D. (Tarjih : Agribusiness Development Journal, 2024)
BumDes Agrotourism Petik Melon faces significant challenges, including intense competition with similar businesses and increasing consumer demands for high-quality tourism experiences. This study aims to analyze the impact of business ethics and social responsibility on consumer satisfaction at BumDes Agrowisata Petik Melon in Balongwono, Trowulan Mojokerto. Using a quantitative approach, the study explores the significance of the relationships between the variables. Data were collected through questionnaires with purposive sampling. The results show that business ethics and social responsibility positively and significantly affect consumer satisfaction. Simultaneous analysis indicates that these variables have a significant collective effect, with an F-value of 28.765 and a significance level of 0.000 (below 0.05), suggesting that the tested factors significantly contribute to the dependent variable. The coefficient of determination reveals that the regression model explains a substantial portion of the data variability, with an R Square value of 0.672, meaning that the independent variables explain 67.2% of the variability in the dependent variable. This research highlights the significant impact of business ethics and social responsibility on consumer satisfaction, suggesting that consumers value ethical business practices and social responsibility, which in turn enhance their satisfaction with services. The novelty of this study lies in its focus on the role of ethics and social responsibility in agrotourism, providing new insights into rural business strategies. Future research could broaden the scope by exploring additional variables like environmental sustainability, expanding the sample size, and comparing multiple agrotourism locations for generalizability.